THE USE OF PODCAST IN LEARNING ENGLISH LISTENING COMPREHENSION - Kamilia, Adila; Zakiah Saadah Alqosimi, Syifa (UIN Sunan Gunung Djati Bandung, 2024)
This study aims to determine the use of podcasts in learning English listening comprehension. Descriptive design and qualitative is used as a method in this study. The population in this study were a class of English education postgraduate students. The data of the research is the process of making the materials, beginning from preparing the topic, recording the conversation, questions-answers until designing the questions for the deep understanding. The data were collected through test, interviews, note-taking and documentation. The result shows that the use of podcasts in learning English listening comprehension can boost the learner’s autonomy and understanding. The students can produce the object for listening, they can listen to it for speaking all at once. In conclusion, the researchers suggest continuing the program since it uses the up-to-date way of learning by optimizing it using technology.